The business of things architecture. Issue 4 (7th May 2013) - Cabral Pinto, F.; Chainho, P.; Pássaro, N.; Santiago, F.; Corujo, D.; Gomes, D.; Antón‐Haro, Carles; Lestable, Thierry; Lin, Yonghua; Nikaein, Navid; Watteyne, Thomas; Alonso‐Zarate, Jesus
ABSTRACT A revolution is happening that is triggered by a brave new world made by interconnected devices. The internet of things is already a reality that is creating new business opportunities across different industrial sectors. Communication service providers have a major opportunity to shape this reality by leading this transformation. For that, they need to evolve their existing architectures to enable a flexible creation of advanced services over distributed networks, interconnecting heterogeneous sensors and actuators. This paper presents an approach for telecoms to take advantage of the upcoming machine‐to‐machine markets and defines an advanced architecture able to withstand the demands of a new plethora of evermore clever and useful services. Copyright © 2013 John Wiley & Sons, Ltd.